2012
DOI: 10.21161/mjm.33911
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of combined disc method for the detection of metallo-β-lactamase producing Gram negative bacilli

Abstract: Infections due to metallo-β-lactamase (MBL) producing Gram negative rods are a cause of high mortality and morbidity. Early detection by an economical and accurate method may improve patient outcome. This study was aimed to evaluate the diagnostic accuracy of combined disc method for MBL detection by comparing it with MBL-Etest. Methodology and Results: This cross-sectional, validation study was carried out in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
3
6
0
Order By: Relevance
“…We found that all isolates found to be MBL positive by CDT were also positive with the E Test and one isolate which were positive by E Test, were found to be MBL negative by CDT. These findings are consistent with the study done by Maria Omair et al 17 The CDT detected 48.2% of MBL producers among which were negative by the DDST and DPT. This may be because the sensitivity varies with the distance between the discs and the antibiotic discs chosen for the test.…”
Section: Discussionsupporting
confidence: 93%
“…We found that all isolates found to be MBL positive by CDT were also positive with the E Test and one isolate which were positive by E Test, were found to be MBL negative by CDT. These findings are consistent with the study done by Maria Omair et al 17 The CDT detected 48.2% of MBL producers among which were negative by the DDST and DPT. This may be because the sensitivity varies with the distance between the discs and the antibiotic discs chosen for the test.…”
Section: Discussionsupporting
confidence: 93%
“…The resistance to these compounds is mediated by a combination of different mechanisms; with enzymatic hydrolysis, mediated by carbapenemases being the most important mechanism of resistance. Carbapenem hydrolyzing enzymes can be divided into two main sub types; Serine β-lactamases (Ambler class A and D) and metallo-β-lactamases (MBLs) (Ambler class B) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Metallo-β-lactamases are one of the most worrisome resistance mechanisms because in addition to limiting treatment options, their genes are carried on highly mobile elements, allowing easy dissemination [6]. Strains producing MBLs are recorded to be responsible for prolonged HAIs outbreaks associated with serious infections [4]; together with higher morbidity and mortality [7].…”
Section: Introductionmentioning
confidence: 99%
“…Another probable explanation mightbe the susceptibility of some bacterial strains to EDTA, which could affect permeability of bacterial membrane, resulting in false positive results of phenotypic tests used for the MβLs detection (Karthika et al, 2009;Aktas and Kayacan, 2008). In general, phenotypic method, especially DDST is reported to be sensitive for detection of MβLs due to wide genetic varieties among gram negative bacilli isolated from clinical samples (Omair et al, 2012).…”
Section: Resultsmentioning
confidence: 99%